Mechanisms of investor attention in enhancing ESG performance: evidence from Chinese listed companies - DanLu, Lu; Tiantian, Meng; Yeng, Wai Lau; Tze, San Ong (Discover, 2025)
In the context of China’s “Dual Carbon” goals and regulatory requirements, listed companies in China are actively engaging in ESG (Environmental, Social, and Governance) practices, and the improvement of ESG performance has become a hot topic in the academic community. This study aims to clarify the impact of investor attention on the ESG performance of listed companies in China and its mechanism of action, depicting a more comprehensive analytical framework compared to existing similar studies. The results show that there is a significant positive correlation between external investor attention and company ESG ratings. Investor attention can positively affect a company’s ESG performance by alleviating financial constraints, increasing R&D spending, and strengthening customer relationships, among other ways. In addition, factors such as the company’s ownership structure, digitalization process, separation of the chairman and CEO positions, and audit quality also play a moderating role in this relationship. Finally, this study provides profound policy recommendations for stakeholders such as investors, companies, and policymakers, aiming to promote companies to effectively enhance ESG performance and promote sustainable development.